Pendampingan Penghitungan dan Pelaporan Pajak Penghasilan Pasal 21 Orang Pribadi pada Civitas Akademika Sekolah Pelayaran Surabaya - Acynthia Ayu Wilasittha; Putri, Sofie Yunida; Tantina Haryati (Universitas Muhammadiyah Malang, 2024)
Purpose – This community service activity aims to enhance the understanding of individual taxpayers in the field of taxation, specifically in calculating and reporting their taxes online. The community service activity took place at Bhakti Samudera Maritime School located in Surabaya, and the participants were teachers and administrative staff from the school. Design/methodology/approach - The activity was conducted in three phases: questionnaire distribution, training on the calculation and reporting of Article 21 Personal Income Tax (PPh Pasal 21), and assistance in calculating and reporting taxes online. Based on the questionnaire data, it was determined that the academic community had income below the Taxable Income Threshold (PTKP). Therefore, the community service team prepared simplified materials for tax calculation and reporting. Findings – This community service activity improved the understanding of individual taxpayers, specifically the academic community of Bhakti Samudera Maritime School in Surabaya, regarding how to calculate their tax liabilities under Article 21 Personal Income Tax and report them using online e-filing. Originality/value – The school's academic community benefited from the training and assistance provided, as it resolved all tax-related issues and misunderstandings.